Mature tau pathology is not improved by interfering with interleukin-1 receptor signaling in two mouse models of tauopathy - Dylan J. Finneran; Brianna M. Jackman; Taylor Desjarlais; Alayna Henry; Ahlam S. Soliman; Patricia C. Muskus; Rama Shankar; Bin Chen; Kevin R. Nash; Dave Morgan; Marcia N. Gordon (PLoS ONE, 2025)
Prior work suggests that the cytokine interleukin-1β (IL-1β) may be a key regulator of tau pathology in the presence of amyloidosis. Here, we tested the possible benefits of interleukin-1 receptor antagonist (IL-1RA) gene therapy in two mouse models of tauopathy. We performed intracranial injections in the rTg4510 model, achieving approximately 300-fold over-expression in the hippocampus, and systemic injections in the PS19 model, resulting in approximately 10-fold over-expression. In neither model did we find substantial treatment effects with IL-1RA over-expression. We found large increases in Il1b gene expression in these mouse models, but considerably smaller increases in IL-1β protein. These data suggest that interleukin-1 receptor antagonist may not be a viable therapeutic strategy for pure tauopathies but cannot rule out possible benefits in amyloid-enhanced tauopathy, which appear to have larger elevations of IL-1β.